2021
DOI: 10.1152/ajpheart.00794.2020
|View full text |Cite
|
Sign up to set email alerts
|

GsMTx-4 normalizes the exercise pressor reflex evoked by intermittent muscle contraction in early stage type 1 diabetic rats

Abstract: Emerging evidence suggests the exercise pressor reflex is exaggerated in early-stage type 1 diabetes mellitus (T1DM). Piezo channels may play a role in this exaggeration since blocking these channels attenuates the exaggerated pressor response to tendon stretch in T1DM rats. However, tendon stretch constitutes a different mechanical and physiological stimuli than that occurring during muscle contraction. Therefore, the purpose of this study was to determine the contribution of Piezo channels in evoking the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…(2) found that T1D patients achieved a higher maximal exercise BP with a similar workload in a cycle ergometer test when compared with control subjects. Previous studies also demonstrated that untreated T1D rats have an exaggerated BP and cardioaccelerator response to static (24) and intermittent (10,11) hindlimb contractions. Determining the underlying mechanisms for an augmented BP response to exercise in T1D is an intriguing area of research, and alterations in the neural control of the cardiovascular system during exercise have been largely implicated.…”
Section: Autonomic Control Of the Circulation In Type 1 Diabetesmentioning
confidence: 86%
See 2 more Smart Citations
“…(2) found that T1D patients achieved a higher maximal exercise BP with a similar workload in a cycle ergometer test when compared with control subjects. Previous studies also demonstrated that untreated T1D rats have an exaggerated BP and cardioaccelerator response to static (24) and intermittent (10,11) hindlimb contractions. Determining the underlying mechanisms for an augmented BP response to exercise in T1D is an intriguing area of research, and alterations in the neural control of the cardiovascular system during exercise have been largely implicated.…”
Section: Autonomic Control Of the Circulation In Type 1 Diabetesmentioning
confidence: 86%
“…The precise mechanism mediating the exaggerated pressor reflex in T1D is not fully understood; however, Piezo channels likely play an important role (9). Of notable interest, studies have shown that GsMTx-4 is able to attenuate the mechanoreflex in rats who are healthy (52), have peripheral artery disease (simulated) (53), or have T1D (9,11). From a translational perspective, however, future research is required to determine the potential role of Piezo channels as a therapeutic target to ameliorate the exaggerated cardiovascular response to muscle contraction in diabetes.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few drugs have been used in pharmacological studies of Piezo1 channel Non-specific inhibitors, broadly classified as Gd3 + , Dooku1, and La3 + in the lanthanide family, gentamicin and streptomycin in the aminoglycoside group, ruthenium red (RR) and the spider venom peptide GsMTx-4 isolated from tarantula toxin (16, 32, 56-60). GsMTx-4 is a cation channelspecific blocker that not only blocks Piezo1 ion channels but also has the effect of inhibiting Piezo1-induced mechanically activated (MA) current generation (61)(62)(63)(64). Mechanistically, GsMTx4 binds to the cell membrane and, by inserting its hydrophobic domain into the lipid bilayer, acts directly on the backbone proteins of the membrane, blocking mechanical force transmission by altering the tension in the membrane and thus achieving a blockade of the Piezo1 ion channel (62,65,66).…”
Section: Piezo Channel Non-specific Inhibitormentioning
confidence: 99%
“…Using this model, we found that the pressor and renal sympathetic nerve activity (RSNA) response to 30 seconds of dynamic muscle stretch was larger when evoked from hindlimb muscles associated with a chronically ligated femoral artery compared to responses evoked from the contralateral hindlimb muscles which were freely perfused (31). Moreover, rat femoral artery ligation was found recently to have no effect on L 4 and L 5 dorsal root ganglia (DRG) protein expression of piezo channels (11), a novel class of MA channel that has been suggested to underlie mechanoreflex activation (10,11,21,22,56). Together, these findings suggest that the exaggerated mechanoreflex in rats with a ligated femoral artery is due, at least in part, to a chronic or persistent sensitization of MA channels located on the sensory endings of thin fiber muscle afferents.…”
Section: Introductionmentioning
confidence: 99%